Doping and Surface Effects of CuFeS2 Nanocrystals Used in Thermoelectric Nanocomposites. Issue 9 (11th July 2018) - Vaure, L.; Liu, Y.; Cadavid, D.; Agnese, F.; Aldakov, D.; Pouget, S.; Cabot, A.; Reiss, P.; Chenevier, P.
Abstract: In the search for low‐cost thermoelectric materials operating near room temperature, the potential of chalcopyrite (CuFeS2 ) nanocrystals is explored. Their colloidal synthesis is optimized to achieve around 40 nm sized nanocrystals with the goal to effectively reduce thermal conductivity via phonon scattering while maintaining high electrical conductivity. EDX and XPS analyses reveal that the nanocrystals are intrinsically nanostructured with a radial compositional gradient. Three strategies are explored to optimize the thermoelectric properties: i) Intrinsic doping by varying the Cu : Fe ratio. However, the effect of this variation is overcompensated by a global sulfur deficiency, making the chalcopyrite nanocrystals n‐type. A high Seebeck coefficient, S, up to −380 μV/K is obtained, while the figure of merit remains comparably low (ZT=0.07 at 400 °C) because of low electrical conductivity σ. ii) Removal of the native, insulating ligands by exchange with potassium selenide. This results in a better trade‐off between S and σ and hence a strongly improved ZT (0.18 at 400 °C). iii) Extrinsic doping via intimate mixture of chalcopyrite nanocrystals with metal nanoparticles. Sn (3 wt %) or Ag (16 wt %) nanoparticles give the best results (ZT=0.16 at 400 °C), inducing the concomitant reduction of thermal conductivity κ and increase of σ. Abstract : Colloidal nanocrystals provide multiple ways to dope thermoelectric nanocomposites: Chalcopyrite CuFeS2 nanocrystals with an optimal size of around 40 nm are hot‐pressed into n‐type, low cost thermoelectric composites. Efficient doping is obtained either through the intrinsic radial compositional gradient in the pristine nanocrystals, by surface ligand exchange with K2 Se, or by blending with metal nanoparticles, leading to 2–3 fold enhancement of the factor of merit ZT.